Impact of traffic variability on geographic accessibility to 24/7 emergency healthcare for the urban poor: A GIS study in Dhaka, Bangladesh - Ahmed, Shakil; Adams, Alayne M.; Islam, Rubana; Hasan, Shaikh Mehdi; Panciera, Rocco (PLOS ONE, 2022)
This article was published in The Plos One [ © 2019 Ahmed et al. This is an open access article distributed under the terms of the Creative Commons Attribution License] and the definite version is available at: https://doi.org/10.1371/journal.pone.0222488. The Journal's website is at: https://journals.plos.org/plosone/article?id=10.1371/journal.pone.0222488